ENHANCING ACCOUNTING INFORMATION SYSTEMS: THE ROLE OF USER COMPETENCE, INTERNAL CONTROLS, AND BUSINESS PROCESSES - Permata, Nurul Intawaty; Rapina, Rapina Rapina; Martusa, Riki; Meythi, Meythi; Darmasetiawan, Johannes Buntoro (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
The quality of Accounting Information Systems (AIS) plays a crucial role in the effectiveness and efficiency of organizational operations. A high-quality AIS ensures accurate and timely financial information, which is essential for strategic decision-making. This study aims to examine the influence of user competence, internal control, and business processes on the quality of Accounting Information Systems (AIS). The sampling technique used convenience sampling with a sampling of 84 respondents. The analysis method used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that (1) user competence had no significant effect on on the quality of AIS, (2) internal control and business process had significant and positive influence on the quality of AIS